The Influence Of Customer Relationship Management And Location On Purchase Intention At Caffe Kokoday East Lombok - Nela Febiola; Akhmad Saufi (LP2M IAIN Palopo, 2026)
This study examines the influence of Customer Relationship Management (CRM) and location on purchase intention at Caffe Kokoday, East Lombok. Amidst the growth of Indonesia's food and beverage sector, the research tests whether CRM practices and strategic location significantly affect consumer purchase intention in the café industry.This descriptive quantitative study employed purposive sampling of 100 respondents who had visited Caffe Kokoday. Data were collected through structured questionnaires measuring CRM (acquire, enhance, retain), location (accessibility, visibility, traffic, parking, environment), and purchase intention (transactional, referential, preferential, exploratory interest). Multiple linear regression analysis was conducted using SPSS, preceded by classical assumption tests.The findings reveal that both CRM and location significantly influence purchase intention. The regression equation Y = -1.715 + 0.675X₁ + 0.435X₂ demonstrates that CRM (t = 4.761, Sig. 0.000 < 0.05) and location (t = 5.561, Sig. 0.000 < 0.05) have positive and significant effects. The coefficient of determination (R² = 0.820) indicates that 82% of purchase intention variance can be explained by these variables, while 18% is attributed to other factors. CRM scored highest on staff service responsiveness (mean = 4.41), while location scored highest on parking accessibility and environmental safety (mean = 4.35).The study confirms that effective CRM and strategic location are critical determinants of consumer purchase intention in cafés. Practitioners should prioritize relationship-building initiatives and accessible locations with adequate facilities. These findings support relationship marketing theory and retail location theory in the food service context. Future research should explore additional variables such as product quality and digital marketing to provide comprehensive understanding of purchase intention drivers.